Improvement of a System for Forecasting Power Generation for Photovoltaic Parks - Israel Borrajero Montejo; Alfredo Roque Rodríguez; Juan Carlos Peláez Chávez; Miguel Hinojosa; Krystine Naranjo Villalón; Maibys Sierra Lorenz (Revista Científica de Ingeniería Energética, 2023)
In this investigation a set of experiments has been carried out consisting on changing parameters on the configuration of the WRF numerical weather forecast model, and evaluating error figures on the 24 hours power generation forecasts at twenty PV parks for a series of 40 selected days between April and June of 2020. The forecasts have been implemented using the solar radiation output of the SisPI forecast system implemented at the Center of Physics of the Atmosphere from the Institute of Meteorology in Havana, Cuba; which is based on the WRF model. The generation forecast was initiated using the operational configuration of WRF, which is optimized mainly to produce the best precipitation forecasts, particularly convective precipitation. The experiments undertaken in this study, allowed to define a new configuration scheme that improves the solar radiation and, subsequently, the power generation forecasts.